Efektivitas Perhitungan Zakat dalam Meningkatkan Kepatuhan Pembayaran Zakat di Desa Pentadio Barat - Valentina Monoarfa; Mohamad Aymar; Muhammad Alghifari Dunggio; Sahril Karelv (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to analyze the effectiveness of zakat calculation in improving zakat payment compliance in Pentadio Barat Village. Zakat is a fundamental obligation in Islam which includes zakat fitrah, zakat on gold, and zakat on deposits/savings. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with muzakki (zakat payers) in Pentadio Barat Village. The interview results show that most of the community has understood the obligation of zakat fitrah and knows the time of its implementation, namely during the period of sunset on the eve of Eid al-Fitr until before the Eid prayer. The distribution of zakat fitrah in the local environment runs in an orderly manner through the management of the mosque committee. Regarding gold zakat, the community has initial awareness but still needs further guidance on nisab calculations. Meanwhile, for deposit zakat, people know the obligation of 2.5% of savings that have reached the nisab and haul of one year. The study concludes that the effectiveness of systematic zakat calculation and continuous socialization contributes positively to increasing muzakki compliance.